Doação de Embriões: diálogo entre Teologia e Biodireito - Almeida, William de (2014)
The main objective of this dissertation is to discuss about the theme Donation of Embryos , by establishing a connection between the Theology and the BioLaw sciences. The hypothesis behind this study is that both views are essential to analyse the value of life, which is the most precious gift of God. This issue will be discussed by using, essentially, studies on the Theology, Bioethics and BioLaw areas. For a better understanding of the subject, three chapters concerned with the concepts of "See, Judge and Act" will be developed. Thus, the first chapter will discuss the doctrine of the church about life and the evolution of human rights , as well as the Law view about protection of human life . The second chapter will analyse the Theological, Bioethics and Law views on donation of embryos and their impact on society . Last, but not least, the third chapter will suggest pastoral lanes and, particularly, a dialogue-path between Theology and Law regarding to the theme Donation of Embryos